Electrostatic and hydrophobic interactions in NaCMC aqueous solutions: effect of degree of substitution - Gonzalez,Lopez C; Colby,R; Cabral,JP (Macromolecules, 2018)
The rheology of water soluble polyelectrolytesat intermediate and high concentrations is controlled byentanglements, hydrophobic and electrostatic interac-tions, whose influence is difficult to isolate. We investi-gate the rheology of semidilute solutions of sodium car-boxymethyl cellulose (NaCMC) with molecular weightMw'2.5×105g/mol and varying degree of substi-tution (D.S.) as a function of polymer concentration invarious solvent media: salt-free water (long ranged elec-trostatic interactions), 0.5M aqueous NaCl (screenedelectrostatics) and 0.5M aqueous NaOH (screened elec-trostatics, diminished hydrophobic interactions) in or-der to selectively probe the different interactions. De-creasing D.S. is found to decrease solubility and inducepartial aggregation and eventual gelation. In salt-freeand 0.5M NaCl solution, NaCMC with D.S.'1.2 ex-hibits hydrophilic polyelectrolyte and neutral polymerin good solvent behaviour respectively. Decreasing D.S.to'0.7-0.8 leads to hydrophobic behaviour in bothsolvents, becoming weak gels at high concentrations. In0.5M NaOH (pH = 13.5) the viscosities of samples withdifferent D.S. become identical when plotted againstthe overlap parameter, which we interpret as result-ing from the solubilisation of unsubstituted celluloseblocks. Small angle neutron scattering (SANS) data in-dicate that the polymer conformation is not stronglyaffected by hydrophobic interactions. By varying D.S.,ionic strength and pH, we demonstrate the tuning ofNaCMC-solvent interactions, controlling separately the electrostatic and hydrophobic effects on the solutionrheology.